The Clinical Performance of Activa Bioactive Composite Compared to Composite in Restoring Class II Cavities in Primary Teeth: 1 Year of Split-Mouth Randomized Clinical Trial - Shihabi, Safaa; AL-Monaquel, Mohammed Bashier; Comisi, John C. (European Journal of Dentistry, 2025)
To evaluate the clinical performance of ACTIVA BioACTIVE compared with traditional composite in restoring class II cavities in primary teeth.In a split-mouth study design, 40 class II restorations were randomly assigned and placed in 20 children aged 6 to 9. The necessary restorations were applied according to the manufacturer's instructions. Over 12 months, two calibrated and blinded evaluators assessed the restorations at 6, 9, and 12 months using the United States Public Health Service Ryge criteria. The Wilcoxon test was used to analyze the difference in success rates between Activa bioactive composite and traditional composite after 6, 9, and 12 months, and multinomial logistic regression was also used to determine the effect of the degree and position of the caries on the success rate.After 6, 9, and 12 months, the 40 restorations were evaluated. The clinical success rates for ACTIVA and composite were 95 and 85%, respectively, after 6 months, with no statistically significant difference. However, a statistically significant difference was observed after 9 months, with success rates of 90% for ACTIVA and 50% for composite (p-value: 0.005). The final success rates were 85 and 45%, with no significant difference. Multiple logistic regression indicated a connection between success rates, the extent of caries, and whether the caries were located on the first or second molars. However, the restoration's location in the upper or lower jaw, as well as whether it was in the mesial or distal area, had no effect on the success rate.ACTIVA Bioactive composite may serve as a viable option for restoring primary teeth; however, further studies with longer follow-up periods and larger sample sizes are necessary.Using ion-releasing materials can enhance clinical restorative success as documented in this clinical study.
Keywords: bioactive composite; composite; bulk-fill; class II cavities; success percentage; clinical performance; remineralization